1955
DOI: 10.1083/jcb.1.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Cell Structure and the Metabolism of Insect Flight Muscle

Abstract: The biochemical properties of housefly flight muscle have recently been investigated to ascertain the mechanisms whereby energy is made available for the contractile processes (Sacktor, , a and b, 1954. These observations demonstrated the complete oxidation of some citric acid cycle intermediates in the sarcosomes (mitochondria) of these muscles, and showed that this oxidation could be coupled with synthesis of the energy-rich phosphate bonds in ATP. 1 Notwithstanding the multitude of enzymes in the mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

1960
1960
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(23 citation statements)
references
References 17 publications
(12 reference statements)
0
22
0
1
Order By: Relevance
“…At the same time the oxygen consumption rises rapidly (Finch & Birt, 1962), the amounts of adenosine triphosphate (ATP) and arginine phosphate (both of which are present almost entirely in the thorax) increase considerably (Crompton & Birt, 1967), and the thoracic mitochondria are capable of reducing nicotinamide-adenine dinucleotide (Birt, 1966). Despite the evidence that blowfly mitochondria are incapable of oxidising fatty acids (Sacktor, 1955), all these data point to the utilization of fatty acids for the provisions of ATP by oxidative phosphorylation. This conclusion is supported by the demonstration (D'Costa & Birt, 1967) of a carnitine-dependent system capable of oxidizing fatty acids which can be detected in thoracic mitochondria isolated from pharate adults and from flies up to 4 days after emergence.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time the oxygen consumption rises rapidly (Finch & Birt, 1962), the amounts of adenosine triphosphate (ATP) and arginine phosphate (both of which are present almost entirely in the thorax) increase considerably (Crompton & Birt, 1967), and the thoracic mitochondria are capable of reducing nicotinamide-adenine dinucleotide (Birt, 1966). Despite the evidence that blowfly mitochondria are incapable of oxidising fatty acids (Sacktor, 1955), all these data point to the utilization of fatty acids for the provisions of ATP by oxidative phosphorylation. This conclusion is supported by the demonstration (D'Costa & Birt, 1967) of a carnitine-dependent system capable of oxidizing fatty acids which can be detected in thoracic mitochondria isolated from pharate adults and from flies up to 4 days after emergence.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies demonstrated that the citric acid cycle was operational in sarcosomes of the housefly Musca domestica [37] and of the blowfly Phormia regina [8]. In general, oxidation was accompanied by the esterification of inorganic phosphate [37]. Specific patterns of oxidation were explored in the mitochondrial and supernatant fractions of the honey bee Apis mellifera [9].…”
Section: Introductionmentioning
confidence: 99%
“…Suffice it, then, to say here that a phosphorylative glycolytic pathway similar to that in vertebrate tis!lUe has been found in the housefly Musca domestica (58,73), the cockroach Periplaneta americana (74), the pea aphid Macrosiphum pisi (75), and the Bilkworm Bombyx mori (76). The pentose phosphate pathway has been clearly established in housefly tissues (77 to 79), and a similar pathway exists in the pea aphid (75) and the silk worm (76).…”
Section: Conversions Of Stores To Energymentioning
confidence: 97%
“…Weis-Fogh (66) showed that the average flight per formance in the locust required much more energy than was contained in the wing muscles and that flight depended on the large scale mobilization of fuel from the fat body. Sacktor (58) suggested that fats may be converted to acetate in the fat body which would then be transported to the tissue and oxidized via the TeA cycle. This suggestion has received some support from the observation (74) that in the muscle of Periplaneta, butyrate was not oxidized but acetate was rapidly consumed.…”
Section: Conversions Of Stores To Energymentioning
confidence: 99%
See 1 more Smart Citation